TREATMENT PROFILE OF TYPE II DIABETES MELLITUS PATIENTS AT BOJONG RAWALUMBU PUBLIC HEALT CENTER 2021 - Fajar Amirulah Fajar (Jurnal Inovasi Farmasi Indonesia (JAFI), 2022)
Diabetes mellitus is a chronically occurring metabolic disorder or a lengthy illness because the body does not have enough insulin hormones, as a result of problems with the secretion of insulin, the insulin hormone does not work well, and it needs to be administered in precise therapy according to the diabetes diagnosis of Mellitus type-2 diabetes. The purpose of this study is to get a profile of the treatment of tipe-2 diabetes patients in the Bojong Rawalumbu with the period of 2021. This method of research uses a retrospective descriptive research design with a sample number of 74. Results: This research found that there were 42 patients with range of age of 56-65 years old (56.8%), females contribide (55.4%) of the total of participant. Treatment Profile suggest as many (44.6%) using metformin for 33 paricipant,  the number of drugs as many the drugs namely 2 drugs (55.4%) for 41  paricipant, the drugs class namely biguanida as many 74 paricipant (100%), the frequency of administration namely metformin 2x a day as many 33 participant, the dosage form tablets as much 74 (100%) participant. And using combination therapy many 41 participant (55.4%) Conclusion: the most likely treatment profile are combination of two drugs of the biguanida + sulfonilurea